Interactive Application Development Using Augmented Reality Concept for Catalog Tire in Planet Ban Store Pasar Kemis - Rachmat Destriana; Hengki Rusdianto; Denis Chandra Prabowo; Dirgahayu Erri; Jordy Lasmana Putra (Jurnal Teknik Komputer AMIK BSI, 2023)
Currently, the company competes to maximize the role of technology in innovating and developing its business. One of them is PT Planet Ban Pasar Kemis in terms of promoting the latest tire products. In this case, researchers want to change the way Planet Ban promotes which has so far only used a 2D tire catalog by utilizing Android-based AR techniques. This makes it difﬁcult for customers to understand the tire products of PT Planet Ban Pasar Kemis. But with AR, customers only need to scan 2D catalog images with Android to see the tire model into 3D form. The system development method used by researchers is the waterfall method where the sequence and steps of research have been structured by the condition of PT Planet Ban. As for System Analysis and Design, researchers use Uniﬁed Modelling Language or UML methods, while product design uses blenders and unity to apply 2D catalog images into 3D models. To measure the success rate of the application, researchers conducted a testing phase using the black box testing method with results that match the test scenario so that the application can be used according to the needs of the user.